2020
DOI: 10.31234/osf.io/vu47r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What counts? Sources of knowledge in children’s acquisition of the successor function

Abstract: Although many US children can count sets by 4 years, it is not until 5½-6 years that they understand how counting relates to number - i.e., that adding 1 to a set necessitates counting up one number. This study examined two knowledge sources that 3½-6-year-olds (N = 136) may leverage to acquire this “successor function”: (1) mastery of productive rules governing count list generation; and (2) training with “+1” math facts. Both productive counting and “+1” math facts were related to understanding that adding 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…This difference suggests that subset‐knowers’ ability to label Unit Task addition events is likely not due to reasoning about an isomorphism between count list successor relations and set operations. However, consistent with previous findings (Schneider et al, 2021), in a separate GLMM we found no difference in accuracy between these two tasks for CP‐knowers ( β = 0.33, p =0.11). While CP‐knowers’ equivalent performance on these tasks is compatible with Structure Mapping, given this group's chance performance for sets of 4 and 5, and the small size of this effect ( d =0.26) it is possible that such a mapping is fragile at this point in development and may not be deployed by all children.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…This difference suggests that subset‐knowers’ ability to label Unit Task addition events is likely not due to reasoning about an isomorphism between count list successor relations and set operations. However, consistent with previous findings (Schneider et al, 2021), in a separate GLMM we found no difference in accuracy between these two tasks for CP‐knowers ( β = 0.33, p =0.11). While CP‐knowers’ equivalent performance on these tasks is compatible with Structure Mapping, given this group's chance performance for sets of 4 and 5, and the small size of this effect ( d =0.26) it is possible that such a mapping is fragile at this point in development and may not be deployed by all children.…”
Section: Methodssupporting
confidence: 92%
“…Although we might expect lower Next Number performance in comparison to the Unit Task due to response format (free response vs. two‐alternative forced‐choice), we address this issue by exploring whether performance on these tasks differs as a function of CP‐knower status, which would suggest a difference in numerical knowledge, rather than response format. Previous work finds a strong correlation between these two tasks among older CP‐knowers, and this correlation remains when both tasks use an open‐ended response format (Schneider, Sullivan, Guo, & Barner, 2021).…”
Section: Methodsmentioning
confidence: 90%
“…However, knowledge of the cardinality principle alone does not guarantee a child's understanding of the successor function for all numbers. It takes CP-knowers approximately two years to learn the specific successor of every number in their count list, and to learn that all numbers have a successor--learning that is aided by their experience with simple n+1 addition facts in early elementary school (Cheung et al, 2017;R. M. Schneider et al, 2020).…”
Section: The Real Preschoolers Of Orange Countymentioning
confidence: 99%